EFEKTIVITAS PENGGUNAAN METODE TALAQQI TERHADAP KEMAMPUAN MEMBACA AL-QUR’AN PESERTA DIDIK KELAS II MIS PANCANA KAB. GOWA - Dahlan, Resky Amalia; Achruh; Syamsuri (Primer Edukasi Journal, 2025)
This thesis discusses "The Effectiveness of Using the Talaqqi Method on the Ability to Read the Quran of Class II Students of MIS Pancana, Gowa Regency". The objectives of this research are: 1) To determine the ability to read the Quran of Class II Students of MIS Pancana Kab. Gowa, 2) To determine students' ability to read the Quran after using the talaqqi method in class II MIS Pancana Kab. Gowa, and 3) To determine the effectiveness of using the talaqqi method on the ability to read the Quran of Class II MIS Pancana Students, Gowa Regency. The type of research used in this research is quantitative with a Pre-Experimental Design approach with a "One-Group Pretest-Posttest Design" type of design. Sampling was carried out using a saturated sampling technique so that the sample size was 12 students. The research instrument used was a test sheet for the ability to read the Quran. The data analysis used in this research is descriptive and inferential statistical analysis techniques with the help of the SPSS 20 application. Based on the results of the ability to read the Quran before and after using the talaqqi method, there are differences, namely before using talaqqi the highest score was 73 and the lowest was 41 with an avaverage 51,083, whereas after using the talaqqi method the highest value was 83 and the lowest 60 so the average was 72,833. After carrying out calculations to test the hypothesis, the results of this study show that there is a significant difference in the results of the ability to read the Quran between students who were taught before and after using the talaqqi method. This can be seen in the t test analysis which was carried out using the Paired Sample T-test with the help of SPSS 20 showing Thit = -7.917 with Ttable = 2.200. So it can be concluded that the talaqqi method is effective on students' ability to read the Quran in class. II MIS Pancana District. Gowa. The implications of this research are: 1) For MIS educators in Pancana District. Gowa, is able to apply varied learning methods in order to improve students' ability to read the Quran, 2) For schools, add references to improve and increase the quality of learning as well as joint study materials in order to improve the quality of schools, 3) For researchers, increase experience researchers directly about how effective the talaqqi method is on the ability to read the Quran.